Lightwave-Driven Valley Control in Graphene - Lesko, Daniel; Weitz, Tobias; Wittigschlager, Simon; Hommelhoff, Peter (CLEO 2024, Technical Digest Series, 2024)
With circular/linearly polarized bi-chromatic electric fields we drive ω − 2ω phase dependent currents in graphene. Comparison with theory reveals the generation of valley specific currents critical to lightwave electronics.
CRIS-Team Scopus Importer:2024-10-25